Women Writing on the French Riviera Travellers and Trendsetters, 1870-1970. - Lancaster, Rosemary (Faux Titre Ser., 2020)
"Destination for artists and convalescents, playground of the rich, site of foreign allure, the French Riviera has long attracted visitors to its shores. Ranging through the late nineteenth century, the Belle Epoque, the 'roaring twenties', and the emancipatory post-war years, Rosemary Lancaster highlights the contributions of nine remarkable women to the cultural identity of the Riviera in its seminal rise to fame. Embracing an array of genres, she gives new focus to feminine writings never previously brought together, nor as richly critically explored. Fiction, memoir, diary, letters, even cookbooks and choreographies provide compelling evidence of the innovativeness of women who seized the challenges and opportunities of their travels in a century of radical social and artistic change"--